Territories and structural change in peri-urban habitats: Coca Codo Sinclair, China investment and the energy matrix change in Ecuador - Viola Reyes, Carolina (2018)
This article investigates the relationship in inhabited spaces between, on the one hand, economic and political structures and, on the other hand, the processes of social and political production. The case of Ecuador is analyzed, where its new relationship with China is part of the process of accelerated capitalist modernization that has accompanied the golden decade of commodities in Latin America. The work is based on the analysis of the strategies that unfold in space and their effects. First, there is a review of the structural implications of the assertion of modes of extraction as the basis of the accumulation process. Next, the state of the Sino-Latin American relationship is analyzed through investment flows and the expansion of Chinese capital in Ecuadorian territory. In this way, the article explores the fundamentals of the transformation strategy of the energy and productive matrix, which incorporates changes in the technique, but maintains the bases of the economic accumulation: an extractive economy located in the periphery of the system. Finally, the reader can find a case study: the area of influence of the Coca-Codo-Sinclair megaproject, identifying transformations in the habitual dynamics of its populations.